The Optimal Stage of Freezing Human Embryos - Louis, Leniaud; Christophe, Sifer (Current Women's Health Reviews, 2009)
Cryobiology is an essential part of In Vitro Fertilisation programs. Indeed, cryopreservation of human zygote or embryos from the early cleaved-cell stage up to the blastocyst stage is a safe procedure, which has been carried out for the last 25 years. Experience with blastocyst cryopreservation is still limited and pregnancy rates after the use of frozen, thawed blastocysts vary extremely. Recently, vitrification has showed to potentially improve the success of embryo cryopreservation, compared to the slow freezing procedure. However, this technique cannot yet be considered as a routine procedure. This review aims to answer the optimal stage of freezing human embryos.
Keywords: vitrification